Evolving Techniques in the Management of Complex LM Artery Disease - Nichols, Emma Hitt (MD Conference Express, 2014)
Although percutaneous coronary intervention (PCI) and coronary artery bypass grafting (CABG) have been established treatments for coronary artery disease (CAD) for about 30 and 50 years, respectively, techniques to perform these strategies continually evolve [Wijns W et al. Eur Heart J 2010]. In addition, complex cases, including rarely seen lesions or complex vascular anatomy, can introduce challenges to clinicians when determining how to best manage a patient requiring myocardial revascularization.